Immobilized Metal Affinity Chromatography purification (IMAC) of his-tagged CTCF-ZN (zinc fingers domain) protein: a comparison between iminodiacetic acid (IDA) - based sepharose and nitriloacetic acid (NTA) - based agarose - Samad, Maisarah Ab (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Since its introduction, Immobilized Metal Affinity Chromatography (IMAC) has massive development by devising several variants of protocols and metal affinity-based techniques, seeking the best protein separation technique to produce high quality and quantity purified protein. This study utilized two different types of metal affinity ligands with the aim of comparing the effectiveness of purification technique for Histagged CTCF-Zn (Zinc finger domain) protein. Iminodiacetic acid (IDA) and Nitriloacetic acid (NTA) were used to chelate the Ni2+ respectively forming the immobilized metal affinity ligand matrices. Different protocols were used in which column purification was applied in the IDA-based IMAC and batch purification for the latter. By modifying the imidazole concentration in the washing and elution buffers, same buffers were used for both IDA-based and NTA-based IMAC. Through the SDSPAGE and western blot analysis, the IDA-based IMAC demonstrates higher His-tag protein recovery and yield compared to NTA-based IMAC. Furthermore, the high protein retention featured by IDA caused low protein loss in the flow through and after washing. In contrast, NTA-based IMAC resulted in low protein affinity and more Histagged protein escaped before the elutions. The level of purity of the protein was relatively similar for both methods as the His-tagged protein purity was seen to be influenced by the structure of the protein and the imidazole concentration of the buffers.